“METAPHYSICAL” LYRICS: BASIC DEFINITIONS IN MODERN LITERARY STUDIES - Agaponova, Ol'ga Sergeevna (Filologičeskij klass, 2020)
The article analyzes various approaches to the study of “metaphysical” lyrics in modern Belarusian and Russian literary criticism, which can be reduced to four main ones: 1) description of the literary school as a historical phenomenon; 2) identification of the key features of the “metaphysical” style in the work of an individual author and a group of authors; 3) identification of conceptual spheres in the lyric text (being / non-being, life / death, transcendental / immanent, world / person, etc.); 4) mutual relations between the categories “metaphysical, philosophical, meditative, religious, spiritual, intellectual”, etc., considered in the genre and paragenre theoretical field. Special attention in literary criticism is paid to the “metaphysical style”, the main features of which are: intellectualism, wit, complicated metaphorism, presence of a precedent prototext (“the Bible”), appeal (explicit and implicit) of the subject to the transcendental addressee or object (to what is beyond the physical world), meditativeness, philosophicality, tendency to expand the boundaries of time and space, associativity, conceptuality, ordinariness of the experienced “metaphysical” situation, synthesis of arts (poetry and music, poetry and painting, poetry, music and painting), “convergence” of somewhat distant ideas, mysticism, etc. The author of the article concludes that the main vector of research into the phenomenon of “metaphysical” lyrics in the works under analysis is reduced to substantiating the specific intentionality of the lyric subject in relation to the transcendental world: the type of consciousness, the dominant of spiritual search, the position of the subject, etc. Thanks to this intentionality, intellectualism and spirituality manifest themselves as a dominant of aesthetic search on all levels of text organization. The consequence of the designated creative attitude is the presence in the text of stylistic features, represented by rich metaphorization, semantic condensation, obscured meaning, synthesis of discourses, etc. In the conclusion, a hypothesis is posed about the existence of a transcendental or “metaphysical” mode of artistic presentation as a type of aesthetic interpretation, which reflects the existential relationships between the subject of creativity and the “transcendent” world.